(untitled) (Swiss Medical Weekly, 2019)
Mitral regurgitation (MR) is a highly prevalent condition among elderly patients, affecting almost 10% of the general population aged 75 and older. Left untreated, severe MR results in high mortality and frequent hospitalisation for treatment of heart failure. Surgical treatment remains the first-line therapy for symptomatic, severe MR, especially for patients presenting with a primary aetiology. However, a high proportion of patients with MR are turned down for open-heart surgery, mainly due to advanced age, diminished left ventricular function and comorbidities. Thus, percutaneous treatment options have been recently developed as an alternative. In this article, we will review transcatheter interventional techniques at the level of the mitral valve, including implantation technique, indications and clinical results.